Reproductive behavior of youth: theory and key factors - V. A. Filippenko (Вестник университета)
The reproductive behavior concept has been considered, which is the key to personal behavior formation in the context of childbirth and family formation. The analysis of approaches to reproductive behavior has been carried out, due to which main factors influencing reproductive behavior patterns formation have been highlighted. Material provision, the possibility to give children quality education and decent living conditions, the place of family and children in the system of values, as well as cultural norms in the complex influence behavior development in relation to family planning and childbirth. Currently, there is a problem of combining parenthood and the image of a successful careerist, so there is competition between the value aspects. The value of family and parenthood remains high, while the need for children decreases. In addition, psychological motives for having children prevail over economic and social ones. The topic of reproductive letting down contains many sides that need to be subjected to analysis. The difficulty lies in the fact that not only we operate with actual objective data, but also deal with personal and psychological characteristics, which complicates the analysis procedure, so it is necessary to further study the issue.